Transmission patterns of rifampicin resistant Mycobacterium tuberculosis complex strains in Cameroon: a genomic epidemiological study - Matthias Merker; Nkongho F. Egbe; Yannick R. Ngangue; Comfort Vuchas; Thomas A. Kohl; Viola Dreyer; Christopher Kuaban; Jürgen Noeske; Stefan Niemann; Melissa S. Sander (BMC Infectious Diseases, 2021)
Abstract Background Determining factors affecting the transmission of rifampicin (RR) and multidrug-resistant (MDR) Mycobacterium tuberculosis complex strains under standardized tuberculosis (TB) treatment is key to control TB and prevent the evolution of drug resistance. Methods We combined bacterial whole genome sequencing (WGS) and epidemiological investigations for 37% (n = 195) of all RR/MDR-TB patients in Cameroon (2012–2015) to identify factors associated with recent transmission. Results Patients infected with a strain resistant to high-dose isoniazid, and ethambutol had 7.4 (95% CI 2.6–21.4), and 2.4 (95% CI 1.2–4.8) times increased odds of being in a WGS-cluster, a surrogate for recent transmission. Furthermore, age between 30 and 50 was positively correlated with recent transmission (adjusted OR 3.8, 95% CI 1.3–11.4). We found high drug-resistance proportions against three drugs used in the short standardized MDR-TB regimen in Cameroon, i.e. high-dose isoniazid (77.4%), ethambutol (56.9%), and pyrazinamide (43.1%). Virtually all strains were susceptible to fluoroquinolones, kanamycin, and clofazimine, and treatment outcomes were mostly favourable (87.5%). Conclusion Pre-existing resistance to high-dose isoniazid, and ethambutol is associated with recent transmission of RR/MDR strains in our study. A possible contributing factor for this observation is the absence of universal drug susceptibility testing in Cameroon, likely resulting in prolonged exposure of new RR/MDR-TB patients to sub-optimal or failing first-line drug regimens.